K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

14 tháng 6 2020

\(D=\frac{sin4x+sin5x+sin6x}{cos4x+cos5x+cos6x}\)

\(=\frac{\left(sin4x+sin6x\right)+sin5x}{\left(cos4x+cos6x\right)+cos5x}\)

\(=\frac{2sin\frac{4x+6x}{2}.cos\frac{4x-6x}{2}+sin5x}{2cos\frac{4x+6x}{2}.cos\frac{4x-6x}{2}+cos5x}\)

\(=\frac{2sin5x.cos\left(-x\right)+sin5x}{2cos5x.cos\left(-x\right)+cos5x}=\frac{sin5x\left(2.cos\left(-x\right)+1\right)}{cos5x\left(2.cos\left(-x\right)+1\right)}=\frac{sin5x}{cos5x}=tan5x\)

9 tháng 8 2019

\(D=\frac{1+sin2x+cos2x}{1+sin2x-cos2x}=\frac{1+2sinxcosx+2cos^2x-1}{1+2sinxcosx-1+2sin^2x}\)

\(D=\frac{cosx\left(sinx+cosx\right)}{sinx\left(sinx+cosx\right)}=cotx\)

9 tháng 8 2019

\(F=\frac{sinx+sin4x+sin7x}{cosx+cos4x+cos7x}\)

\(F=\frac{2sin4xcos3x+sin4x}{2cos4xcos3x+cos4x}\)

\(F=\frac{2sin4x\left(cos3x+1\right)}{2cos4x\left(cos3x+1\right)}=tan4x\)

NV
23 tháng 4 2021

\(P=\dfrac{-2sin5x.sinx-sinx}{2sin5x.cosx+cosx}=\dfrac{-sinx\left(2sin5x+1\right)}{cosx\left(2sin5x+1\right)}=-tanx\)

25 tháng 8 2020

\(C=\frac{\cos4x.\tan2x-\sin4x}{\cos4x.\cot2x+\sin4x}\)

\(=\frac{\cos4x.\sin2x-\sin4x.\cos2x}{\cos4x.\cos2x+\sin4x.\sin2x}.\frac{\sin2x}{\cos2x}\)

\(=\frac{\sin\left(2x-4x\right)}{\cos\left(4x-2x\right)}.\frac{\sin2x}{\cos2x}=-\frac{\sin^22x}{\cos^22x}=-\tan^22x\)

14 tháng 10 2018

Chọn A.

Ta có:

+ sin4x + cos4x = (sin2x + cos2x)2 - 2sin2x.cos2x = 1 - 2sin2x.cos2x.

+ sin4x + cos4x = 1 - 3sin2x.cos2x.

Do đó

A = 3(1 - 2sin2x.cos2x) - 2(1 - 3sin2x.cos2x) = 1.

15 tháng 6 2016

A=\(\frac{\left(cos7x+cos10x\right)-\left(cos8x+cos9x\right)}{\left(sin7x+sin10x\right)-\left(sin8x+sin9x\right)}\) =\(\frac{2cos\frac{17x}{2}.cos\frac{3x}{2}-2cos\frac{17x}{2}.cos\frac{x}{2}}{2sin\frac{17x}{2}.cos\frac{3x}{2}-2sin\frac{17x}{2}.cos\frac{x}{2}}\)

=\(\frac{2cos\frac{17x}{2}\left(cos\frac{3x}{2}-cos\frac{x}{2}\right)}{2sin\frac{17x}{2}\left(cos\frac{3x}{2}-cos\frac{x}{2}\right)}\)=\(\frac{cos\frac{17x}{2}}{sin\frac{17x}{2}}\)=cotg\(\frac{17x}{2}\)

 

NV
28 tháng 4 2021

\(=\dfrac{1}{2}sin6x-\dfrac{1}{2}sin2x-\left(\dfrac{1}{2}sin4x-\dfrac{1}{2}sin2x\right)\)

\(=\dfrac{1}{2}sin6x-\dfrac{1}{2}sin4x\)

\(=cos5x.sinx\)

11 tháng 5 2022

gt rõ hơn được không ạ, e k hiểu lắm ạ

19 tháng 5 2019

\(A=\frac{cos7x-cos8x-cos9x+cos10x}{sin7x-sin8x-sin9x+sin10x}=\frac{(cos10x+cos7x)-\left(cos9x+cos8x\right)}{\left(sin10x+sin7x\right)-\left(sin9x+sin8x\right)}.\) 

     \(=\frac{2cos\frac{17x}{2}cos\frac{3x}{2}-2cos\frac{17x}{2}cos\frac{x}{2}}{2sin\frac{17x}{2}cos\frac{3x}{2}-2sin\frac{17x}{2}cos\frac{x}{2}}=\frac{2cos\frac{17x}{2}\left(cos\frac{3x}{2}-cos\frac{x}{2}\right)}{2sin\frac{17x}{2}\left(cos\frac{3x}{2}-cos\frac{x}{2}\right)}=cotan\frac{17x}{2}.\)  

5 tháng 3 2019

Chọn C.

Ta có

C = [ ( sin2x + cos2x) – sin2cos2x]2 - [ ( sin4x + cos4x) 2 - 2sin4x.cos4x]

= 2[ 1-sin2x.cos2x]2 - [ ( sin2x + cos2x) 2 - 2sin2x.cos2x]2 + 2sin4x.cos4x

= 2[ 1-sin2x.cos2x]2 - [1-sin2x.cos2x]2 + 2sin4x.cos4x

= 2( 1 - 2sin2x.cos2x + sin4x.cos4x)- ( 1 - 4sin2xcos2x + 4sin4x.cos4x) + 2sin4x.cos4x

= 1.